Base-temperature for estimation of the days-degree for soybean cultivars in São Paulo State, Brazil - Camargo, Marcelo Bento Paes de; Brunini, Orivaldo; Miranda, Manoel A. Coelho de (Pesquisa Agropecuaria Brasileira, 2014)
The summation of degree-days necessary to complement the phenological phase from planting to ripening was estimated for different soybean (Glycine max (L.) Merrill) cultivars, under the conditions of São Paulo State, Brazil. The study was performed in the phenological dates obtained of experiments was conducted by Leguminous Section of the Instituto Agronômico in Campinas, Ribeirão Preto and Pindamonhagaba, in, three agricultural years. An analysis of the relationship between air temperature and crop development indicate that the base-temperature for the phenological phase from planting to ripening was 14ºC for all cultivars. It was also observed that the total degree-days necessary was 1336, 1275, 1227 and 1030, respectively for the UFV-1, Santa Rosa, Viçosa and Paraná cultivars.